The Influence of Contextual Learning Approach Loaded with Cultural Values on Student Learning Outcomes - Kadek Hengki Primayana; IG Agung Jaya Suryawan (Edukasi: Jurnal Pendidikan Dasar, 2022)
This study aims to determine the differences between students who are taught with conventional learning models and students who are given contextual learning models. Real results are obtained from all the concepts obtained and their relation to other concepts studied and make learning activities more meaningful. This is expected to result in the ability of students to be able to apply their learning gains to solving real problems in their lives, learning through direct experience, in contextual learning containing National Cultural Values programmed to involve students directly in the concepts and principles being studied and enabling students learn by doing activities directly. So that students will understand their learning outcomes in accordance with the facts and events they experience, not just information from the teacher and pay more attention to the process than the result.